Be tough: masculine identities and viral load suppression among adolescent boys on antiretroviral therapy in Siaya County, Kenya - Peter, Simon; Nyambedha, Erick Otieno; Olang’o, Charles Omondi (International Journal Of Community Medicine And Public Health, 2025)
Background: Viral load suppression among adolescent boys is critical in the fight against HIV and AIDS globally. Contrary to the reduction noted in other age groups, mortality among adolescents aged 14-19 related to AIDS has continued to rise worldwide. This age group recorded 41,000 deaths in 2020 up from 18,000 in 2010, with boys constituting 69%. In Siaya County, 68% of AIDS-related deaths occurring among 14-19 adolescents in 2020 were boys. Although men’s poor health outcomes have been linked to masculinities, a paucity of literature exists on how this extends to adolescent boys. This paper sought to investigate how endorsement of masculine identities has influenced VL suppression among adolescent boys on ART in Siaya County of Kenya. Methods: This cross-sectional study used questionnaire to collect data from 263 adolescent boys on ART. Six focus group discussions were held with the boys and another six with PBO officials, while six in-depth interviews and five key informant interviews were respectively held with selected adolescent boys and healthcare practitioners and government officers. Results: Endorsement of masculine identities were found to have a negative influence (B=-0.323; p=0.000) on VL suppression, significantly contributing to an estimated 24.8%-unit changes (R2=0.248, p=0.000). Conclusions: Socialization to be tough, fearless and aggressive as well as to shun expressing emotions has led to poor attendance of medical appointments and uptake of ART among the adolescent boys, hence negatively affecting VL suppression. Targeted interventions should aim at addressing such barriers among the adolescent boys.